Palmares no cepo da história: história e historiografia da Confederação dos Quilombos dos Palmares (1644-1984) - Silva, Adriano Viaro da (2016)
The aim of this study is to analyze the historical production and review the literature on the quilombos dos Palmares in different periods of our history, designed to further understanding of the ways in which the quilombos of the Serra do Barriga were represented in our historiography. The work uses as method, bibliographic and biographical survey, of each author and their involvement in the historical context in which his works were produced, by confronting the major historiographical productions of each period, for obtaining an analytical result. In the chronological division into chapters, were used landmarks already established by official historiography, as the periods of Colonial Brazil, Imperial and Republican, plus special chapter to the work of Décio Freitas. In the first chapter, were analyzed the primary sources of Dutch origin and the first travel accounts and expeditions to Palmares, which were Dutch, Lusitanian and Luso-Brazilian. In the second chapter, were analyzed the seven most influential works of the period, as well as the articles of the istorical and Geographical Institutes, besides to the textbooks of the College Pedro II, important formative college of the Brazilian elite of the time. The third chapter, comprising the largest number and highest density of historiographical studies, received the longest and most detailed analysis, especially the Marxist production period. The fourth chapter is made up of comprehensive analysis of the work 'Palmares: the war of the slaves', of Décio Freitas, which we understand be the most well finished work until today. Because of this understanding, we analyzed the work of Décio with crosses between its five Brazilian issues, as well as the description of the characteristics and changes in each edition. As a result of this study, we seek a greater understanding of the different objectives and more distinct approaches of each period, emphasizing the changes of representation and highlight, undergone by the historiography of Palmares throughout the history of Brazil, by the year 1984, where we completed the analysis.